2017
DOI: 10.1007/s00355-017-1076-2
|View full text |Cite
|
Sign up to set email alerts
|

Gender and inequality of opportunity in Sweden

Abstract: This paper considers the role of gender in generating inequality of opportunity. Using data on long-run income for Swedish men and women, we explore to what extent income inequality is due to circumstances beyond individuals' control, such as gender and parental income, rather than to differences in individuals' choices. The key idea is that a society has achieved equality of opportunity if there is no income inequality that is due to circumstances. Analyzing men and women separately, we find that circumstance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 45 publications
1
11
0
2
Order By: Relevance
“…In the one study that focused specifically on gender, Hederos et al (2017) found that it explained 13 percent of total inequality, making it the most important circumstantial determinant of long-term income in Sweden -a point that we confirm for the case of China as well. 2 In separate analyses for each gender, they found that circumstances (excluding gender) explain more of male than female income inequality, leading them to conclude that there is greater equality of opportunity among women than men.…”
Section: Analysis Of Individual Labor Earnings In Five Latinsupporting
confidence: 72%
“…In the one study that focused specifically on gender, Hederos et al (2017) found that it explained 13 percent of total inequality, making it the most important circumstantial determinant of long-term income in Sweden -a point that we confirm for the case of China as well. 2 In separate analyses for each gender, they found that circumstances (excluding gender) explain more of male than female income inequality, leading them to conclude that there is greater equality of opportunity among women than men.…”
Section: Analysis Of Individual Labor Earnings In Five Latinsupporting
confidence: 72%
“…Bertrand and Mullainathan, 2004;Lang and Manove, 2011). Unequal opportunities between men and women are equally objectionable (Hederos et al, 2014;Calo-Blanco 8 Unfortunately, the IPUMS USA database does not provide data on the individual components of income. 9 Note that IO measures the extent to which individual income is driven by individual attributes that are beyond the individual's control such as race and gender.…”
Section: The Ipums Usa Database and Sample Designmentioning
confidence: 99%
“…An additional advantage is that it allows analyzing inequality among men and women separately. Indeed, based on numerous studies on different types of socioeconomic inequalities and demographic behavior (Buchmann et al, 2008;Charles and Grusky, 1995;DiPrete and Jennings, 2012;Hederos et al, 2017;Korpi, 2000;Lee and Solon, 2009;Prix, 2009)(e.g., Buchmann, DiPrete, and McDaniel 2008;Charles and Grusky 1995;DiPrete and Jennings 2012;Hederos, Jäntti, and Lindahl 2017;Korpi 2000;Lee and Solon 2009;Prix 2009), it seems reasonable to assume that the mechanisms contributing to inequality are different for men and women (however, see .…”
Section: Selection Into Partnershipsmentioning
confidence: 99%